2011
DOI: 10.1002/ijc.25889
|View full text |Cite
|
Sign up to set email alerts
|

HPV involvement in tonsillar cancer: Prognostic significance and clinically relevant markers

Abstract: The association of high-risk human papillomaviruses (HR HPVs) with tonsillar cancer (TC) has been documented. Because patients with HPV-associated tumors show better survival rates, modification of their treatment regimen is being considered. It is therefore crucial to find markers for the identification of patients whose tumors are linked to viral infection. A cohort of 109 patients with primary TC was screened for HPV DNA presence in the tumor tissues and HPV-specific antibodies in sera. Data regarding risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
71
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 47 publications
14
71
1
2
Order By: Relevance
“…Some studies in Oncology have assessed the predisposition of individuals to the onset of cancer [28][29][30] , which can even predispose them to the recurrence of it, with or without treatment. In the literature, cases of genetic predisposition to cancer of the head and neck areas is not well observed, but cases of genetic alteration acquired through the association of behavioral habits, such as tobacco use 29,31 , alcohol consumption 29,31 , viruses such as HPV 32,33 and even the consumption of red meat 34 . Such findings show that the prevention of this type of cancer becomes more feasible by combating and controlling factors related to habits and associated factors susceptible to intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in Oncology have assessed the predisposition of individuals to the onset of cancer [28][29][30] , which can even predispose them to the recurrence of it, with or without treatment. In the literature, cases of genetic predisposition to cancer of the head and neck areas is not well observed, but cases of genetic alteration acquired through the association of behavioral habits, such as tobacco use 29,31 , alcohol consumption 29,31 , viruses such as HPV 32,33 and even the consumption of red meat 34 . Such findings show that the prevention of this type of cancer becomes more feasible by combating and controlling factors related to habits and associated factors susceptible to intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the HPV testing in exfoliated tumor cells from oral washings has been shown to be a reliable tool for determination the HPV tumor status, with sensitivity and specificity of 0.83 and 0.88, respectively [35]. The detection of anti-E6/E7 antibodies in patients´sera seems to be an other promising method for indirect checking of HPV status of the HNSCCs [40].…”
Section: Discussionmentioning
confidence: 99%
“…The manufacturer´s protocol was modified to adapt the test for use on paraffin-embedded tissue according to Siriaunkgul et al [14]. The test involves three steps: PCR amplification of target DNA, nucleic acid hybridization, and detection of 37 HPV types, specifically 6,11,16,18,26,31,33,35,39,40,42,45 PCR was performed in a total volume of 100 µL containing 50 µL of the manufacturer´s master mix and 50 µL of GP5+/GP6+ PCR product. The amplification program consisted of 2 min at 50°C, and 9 min at 95°C, followed by 40 cycles of 30 s at 50°C, of 1 min at 55°C, and of 1min at 72°C, with a final extension at 72°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that in HNSCC patients, HPV positivity is a strong prognostic factor for both better survival and less frequent recurrent disease [9, 36]. Another study from our group on immunological markers in HNSCC patients has shown higher Tregs counts in the peripheral blood of these patients when compared to healthy controls and increased probability of early recurrence with higher Tregs counts in the peripheral blood [29].…”
Section: Introductionmentioning
confidence: 99%
“…HR HPVs are being detected in 67% of oropharyngeal tumors and now are widely accepted as an etiological factor of 20–25% of head and neck squamous cell carcinomas [7, 8]. As has been shown by us and others, patients with HPV-positive tumors have better prognosis which is an important observation of clinical relevance [9, 10]. …”
Section: Introductionmentioning
confidence: 99%